2023
DOI: 10.1002/cpe.7480
|View full text |Cite
|
Sign up to set email alerts
|

Blood vessel detection using enhanced DeepJoint fuzzy clustering algorithm with deep Maxout network for glaucoma detection

Abstract: Glaucoma became a leading reason for losing vision as it progresses in a gradual manner without any symptoms. The discovery of glaucoma at an earlier phase is imperative as it can help to accelerate the progress. The fundus images are an option for screening glaucoma and help to enable the observation of optic disc. The classical techniques are less accurate and time-consuming. In this way, a highly accurate automatic glaucoma diagnosis is developed in this research. The noise in the images is eliminated durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…According to the article published by Goodfellow et al [38], the Maxout activation function has demonstrated its effectiveness for training with Dropout, as well as its robustness for image classification [39]. Each feature map is dimensionally reduced using a Maxpooling layer with a pool size of 2x2 to preserve the most relevant features identified and avoid unnecessary computations.…”
Section: Learning Spatiotemporal Featuresmentioning
confidence: 99%
“…According to the article published by Goodfellow et al [38], the Maxout activation function has demonstrated its effectiveness for training with Dropout, as well as its robustness for image classification [39]. Each feature map is dimensionally reduced using a Maxpooling layer with a pool size of 2x2 to preserve the most relevant features identified and avoid unnecessary computations.…”
Section: Learning Spatiotemporal Featuresmentioning
confidence: 99%